PENGARUH SUPERVISI DAN KOMPENSASI TERHADAP KINERJA YANG DI MEDIASI VARIABEL MOTIVASI KERJA GURU SMA NEGERI 1 MAUMERE - Mohamad Amir (Universitas muhammadiyah malang, 2017)
This study aims to determine 1) Effect of supervision of principals on work motivation of teachers in SMA Negeri 1 Maumere. 2) The effect of compensation on work motivation of teachers in SMA Negeri 1 Maumere. 3) Effect of supervision of principals on teacher performance in SMA Negeri 1 Maumere. 4) Effect of compensation to the performance of teachers in SMA Negeri 1 Maumere. 5) The effect of work motivation on teacher performance in SMA Negeri 1 Maumere. 6) Role of Motivation as a mediating influence supervision of principals on teacher performance in SMA Negeri 1 Maumere. 7) The role of motivation to work as a mediating influence of compensation on teacher performance in SMA Negeri 1 Maumere. Analysis of the data used in the study using Path Analysis (path analysis) which is the application of multiple regression using the path diagram as a guide t test the hypothesis testing as a basis for decision making in determining the direct and indirect effects of research dependent and independent variables.